Buchans Transmitter Program - Day 2, Tape 8 - Memorial University of Newfoundland. Division of Extension Service (Producer) (Buchans Community T.V. [and] Memorial University School of Continuing Studies and Extension, 1985)
"Entertainment Tonight" program continued with host Peter Evans and band members Wayne Whelan, Art Kennedy, Bob Golding, Neil Hunt and Pat Byrne; as well as Sandy Ivany. Late News wrap up at 8:38 with Kim St. George followed by Sign Off with the Ode to Newfoundland and views of the town of Buchans.